Hybrid alternative protein-based foods: designing a healthier and more sustainable food supply - Kaplan, David L.; McClements, David Julian (Frontiers in Science, 2025)
The industrial scale use of animals to produce food for humans, such as meat, egg, and dairy products, has serious environmental, health, and ethical implications. Livestock production is a major source of greenhouse gas emissions and drives soil depletion, water pollution, deforestation, and biodiversity loss. There are also concerns about its negative impacts on human health and animal welfare. To feed future generations, it will be important to produce nutritious foods in a more sustainable, ethical, and environmentally friendly manner. In this article, we examine several protein-rich food sources as alternatives to traditional animal proteins, including plants, insects, mycelia, cultured animal cells, and microbial fermentation products. Each of these alternative protein sources has advantages and disadvantages in terms of their organoleptic properties, nutritional profile, consumer acceptance, affordability, and scalability. We then consider combining different alternative protein sources to form affordable, scalable, delicious, nutritious, and sustainable hybrid foods that may compete with conventional meat products, including meat–plant, cultivated meat–plant, mycelium–plant, and insect–plant foods. However, these hybrid products are still relatively new, and significant challenges, including cost reduction, scalability, regulatory approval, and consumer acceptance, need to be addressed before they become commercially viable. Future research should therefore focus on optimizing protein sources, developing scalable production methods, conducting environmental and economic analyses, and leveraging artificial intelligence for innovation. To make hybrid food products viable and sustainable, more efficient collaboration across academia, industry, and regulatory bodies is urgently needed.